Gender and political economy: Dimensions of exploitation - S. Venkatanarayanan and Fusari, Valentina (South Asian Journal of Socio-Political Studies)
The centrenched in the social fabric, gender organizes social life and thus muchy of individual experiences.- Reproduced
Keywords: Gender, Neoliberalism, Patriarhy, Labour, Political economy